Endoscopic full-thickness transoral outlet reduction with semicircumferential endoscopic submucosal dissection - Hollenbach, Marcus; Selig, Lars; Lellwitz, Sylvia; Beer, Sebastian; Feisthammel, Jürgen; Rosendahl, Jonas; Schaumburg, Tiffany; Mössner, Joachim; Hoffmeister, Albrecht (Endoscopy, 2019)
Background Endoscopic full-thickness transoral outlet reduction (efTOR) is a therapeutic option to reduce a dilated gastrojejunal anastomosis (GJA) after Roux-en-Y gastric bypass (RYGB). Mucosal ablation with argon plasma coagulation (APC) is usually performed to achieve tissue adaptation. However, rupture of sutures before scarring can lead to recurrent dilatation of the GJA. Here, we describe efTOR with a semicircumferential endoscopic submucosal dissection (ESD-efTOR) as an alternative to APC-efTOR.Methods We enrolled 41 patients with comparable baseline characteristics (APC-efTOR 26; ESD-efTOR 15). The main objectives were reduction in the GJA diameter and in ruptured sutures. Technical success, complications, total weight loss (TWL), and percentage of total and excess weight loss (%TWL and %EWL) at 3 and 12 months, were assessed. Results ESD-efTOR resulted in significantly fewer ruptured sutures (20 % vs. 69 %; P = 0.004) and a greater reduction in the GJA (major 20 % vs. 0 %; minor 54 % vs. 37 %; no reduction 13 % vs. 58 %; P = 0.02) after 3 months. Technical efficacy, examination time, and rate of complications were comparable.Conclusions ESD-efTOR resulted in a significantly greater reduction in the GJA diameter and a lower risk of ruptured sutures compared with APC-efTOR.